Analisis Hukum Agraria Terhadap Peralihan Status SHP Barang Milik Daerah Kota Bengkulu Menjadi HGB Pada Kasus Mega Mall: Studi Kasus Pelanggaran Fungsi Sosial Tanah - M. Adyat Rizky Ananda; Muhammad Farhan Dwi Putra; Andika Wira Pratama; Fatrico Fathan An-Najjah S; M. Bayu Bagir Basil (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
The Mega Mall Bengkulu case has become an important study in the realm of Indonesian agrarian law, which highlights the practice of converting land status from Land Management Rights (HPL) owned by the Bengkulu City Government as a form of management rights over state or regional land according to Article 35 of the UUPA to a Building Use Rights Certificate (HGB) under the private name of PT Trigadi Benggawan (now PT Tigadi Lestari) through Cooperation Agreement Number 640/228/B.VII/2004 along with the 2005 addendum which is suspected to be legally flawed. The conversion is suspected of violating Article 43 of the UUPA, which requires the approval of the competent authority and full compensation, as well as Article 16 of the UUPA concerning land area limitations, because the process sidesteps the role of the regional DPRD and ignores the doctrine of the social function of land as stipulated in Article 6 of the UUPA, which emphasizes land use for the welfare of the wider community, not merely individual interests. This article examines the legal consequences of converting HPL to HGB within the agrarian law framework, including the criminal risks under Article 50 of the UUPA due to the abuse of authority to issue certificates, the lack of state administrative oversight based on Government Regulation Number 40 of 1996 concerning Land Management Rights, and the broad impact on the sustainability of regional assets amidst rampant corruption in the property sector. Furthermore, the discussion includes proposed improvements such as strengthening HPL licensing regulations at the regional level, implementing certificate digitization by the National Land Agency (BPN) to increase transparency, DPRD participation in asset transfer transactions, and implementing agrarian sanctions integrated with corruption crimes to prevent similar incidents, in order to strengthen the social function of land as a foundation for national agrarian justice.